2021
DOI: 10.1080/0284186x.2021.1971294
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study on the neo-adjuvant combination of pazopanib and radiotherapy in patients with high-risk, localized soft tissue sarcoma

Abstract: Purpose: A prior phase I study showed that the neo-adjuvant combination of pazopanib and radiotherapy was well tolerated, and induced promising pathological responses in soft-tissue sarcoma patients. Results of the subsequent prospective, multicenter phase II, PASART-2 trial are presented here, further investigating the efficacy and safety of this combination. Patients and methods: Patients with high-risk, localized soft-tissue sarcoma received neo-adjuvant radiotherapy, 50 Gy in 25 fractions (PASART-2A) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Intending to preserve the limb, surgery with perioperative (pre- or post-operative RT) is the treatment of choice in patients with localized sarcoma ( 22 ). In the present case, neoadjuvant pazopanib was added to radiation to improve the local control rates based on the results of the PASAART-1 and -2 trials ( 8 ). The GI toxicity experienced by the patient soon after starting pazopanib and the resolution of symptoms after stopping elderberry hint towards a possible drug-drug interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intending to preserve the limb, surgery with perioperative (pre- or post-operative RT) is the treatment of choice in patients with localized sarcoma ( 22 ). In the present case, neoadjuvant pazopanib was added to radiation to improve the local control rates based on the results of the PASAART-1 and -2 trials ( 8 ). The GI toxicity experienced by the patient soon after starting pazopanib and the resolution of symptoms after stopping elderberry hint towards a possible drug-drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Pazopanib is approved by the US Food and Drug Administration (USFDA) for patients with metastatic renal cell carcinoma and those with metastatic or locally advanced unresectable soft-tissue sarcoma (STS) who experienced progression after chemotherapy (7). Several trials in patients with localized high-risk extremity STS have also explored the utility of administering neoadjuvant pazopanib with preoperative radiation therapy (RT) with mixed results (8,9). The patient presented in the current study was consuming elderberry supplements when she started pazopanib.…”
Section: Introductionmentioning
confidence: 99%
“…This pharmacokinetic study was embedded in an international, multicenter phase II trial (NCT02575066) [ 5 ]. Written informed consent was obtained, the study protocol was approved by the local ethics commissions and the study was conducted in accordance with the declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Haas et al showed that the neoadjuvant use of pazopanib 800 mg once daily in combination with 50 Gy preoperative radiotherapy (RT) seems tolerable and shows promising results in terms of efficacy also in patients with non-metastatic, intermediate or high-grade STS of the extremities, in the phase I PASART-1 study (NCT01985295) [ 4 ]. The combined treatment regimen was subsequently assessed in the phase II PASART-2 trial (NCT02575066) [ 5 ]. The main efficacy endpoint of this single arm trial was the rate of pathological complete response (pCR), defined as ≤5% viable tumor cells in the resection specimen at central pathology review.…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian retrospective study, Kataria et al reported that, out of four MFS patients, two (50%) had SD and two (50%) had PD [95]. More recently, a prospective multicenter phase 2 trial (NCT02575066, acronym PASART-2) was performed to investigate the efficacy of neo-adjuvant pazopanib and concurrent external beam radiotherapy for high-risk, localized STS [96]. In the NCT02575066 trial, of the 25 patients, 8 (32%) had MFS.…”
Section: Pazopanibmentioning
confidence: 99%